Analisis Keanekaragaman dan Dominansi Tumbuhan Tingkat Tinggi di Kelurahan Silea, Kolaka - Astuti, Widia; Safitri, Tiara; Lista, Lista; Futri, Regina; Saputri, Nabila Aulia; Meicitra, Ketut Arika; Maulia, Tri Putri; Maretik, Maretik (Educatoria : Jurnal Ilmiah Ilmu Pendidikan, 2026)
Plant diversity is an important indicator in describing the condition and stability of an ecosystem. This study aims to determine the diversity, relative abundance, evenness, and dominance of higher plants in Silea Village, Wundulako District, Kolaka Regency. The study used a quantitative descriptive method through field observations with line transect sampling techniques combined with quadrant transects at three observation stations. Data were analyzed using the Shannon-Wiener diversity index (H'), Relative Abundance (KR), evenness index (E), and Simpson dominance index (C). The results showed that 33 species belonging to 29 genera of higher plants were found. The diversity index values ​​at the three stations ranged from 2.14 to 2.50, which is included in the moderate category, while the evenness index ranged from 0.73 to 0.85, which indicates a relatively even distribution of individuals. The highest relative abundances were found, respectively, in Pogostemon cablin (28.99%), Vanilla planifolia (20.00%), and Theobroma cacao (36.17%). Dominance index values ​​ranged from 0.08 to 0.16, indicating the absence of excessively dominant species. Environmental parameters measured included a temperature of 30-31°C, a pH of 6, and a salinity of 78.4-90.1‰. Based on the results, it can be concluded that the higher plant community in Silea Village is relatively stable, with a moderate level of diversity and a relatively even distribution of individuals. These results serve as baseline data for the management, conservation, and monitoring of plant diversity in Silea Village.